2012
DOI: 10.1016/j.rse.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Using microwave brightness temperature diurnal cycle to improve emissivity retrievals over land

Abstract: Reza, "Using microwave brightness temperature diurnal cycle to improve emissivity retrievals over land" (2012 To retrieve microwave land emissivity, infrared surface skin temperatures have been used as surface physical temperature since there is no global information on physical vegetation/soil temperature profiles. However, passive microwave emissions originate from deeper layers with respect to the skin temperature. So, this inconsistency in sensitivity depths between skin temperatures and microwave temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 42 publications
5
34
0
Order By: Relevance
“…Many contributing factors (e.g., soil moisture, superficial profile of soil temperature, and phenology) are required to explain the behavior of the two passive microwave indices in Alice Springs and Sturt Plains. In particular, in these sparse vegetated sites, the observed radiation was not simply produced at the air/soil interface, and FI variations can be explained by variations of temperature profile, in agreement with previous works [Parinussa et al, 2011;Norouzi et al, 2012].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many contributing factors (e.g., soil moisture, superficial profile of soil temperature, and phenology) are required to explain the behavior of the two passive microwave indices in Alice Springs and Sturt Plains. In particular, in these sparse vegetated sites, the observed radiation was not simply produced at the air/soil interface, and FI variations can be explained by variations of temperature profile, in agreement with previous works [Parinussa et al, 2011;Norouzi et al, 2012].…”
Section: Discussionsupporting
confidence: 92%
“…However, over some areas such as sand dunes, small brightness temperature diurnal cycles have been observed, which are not consistent with the diurnal variations of skin temperature [Prigent et al, 1999;Norouzi et al, 2012]. These studies show that in sandy soils, the observed microwave emission comes from deeper layers rather than from the surface skin and the observed signal depends on the frequency and soil temperature profile [Prigent et al, 1999].…”
Section: Introductionmentioning
confidence: 71%
“…However, in some other channels, such as 37V, the differences between TMI and WindSat could reach 3 K (Wilheit, 2013), which can have a non-negligible influence on emissivity estimates. This difference causes about 0.01 difference in emissivity estimates, which is significant especially in regions where emissivity values are higher than 0.95 (Norouzi et al, 2012).…”
Section: Resultsmentioning
confidence: 97%
“…In desert, unlike rain forest regions, maximum differences are at lower frequencies and agreements relatively improve at higher frequencies, particularly in the horizontal polarization values. The deeper penetration of the microwave signal especially at low frequencies in desert which leads to differences in the diurnal amplitude and phase of skin temperature and microwave brightness temperature can introduce considerable error in emissivity retrievals (Norouzi et al, 2012). This issue is more highlighted in desert areas due to moisture scarcity and minimal vegetation interferences.…”
Section: Resultsmentioning
confidence: 99%
“…MW radiometers with a Ka-band channel are available from several low Earth orbiting satellites 30 that sample at different times of the day. Together they can be used to construct a diurnal cycle of brightness temperature for each location on Earth (Holmes et al, 2013b;Norouzi et al, 2012). This diurnal brightness temperature can then be scaled to match the diurnal temperature cycle as measured by TIR imagers (Holmes et al, 2015(Holmes et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%